Tracking Comets and Asteroids Using Machine Learning and Deep Learning: A Review - Khalil, M.; Said, M.; Ibrahim, A.; Gamal, M.; A. Mobarak, M. (International Journal of Advanced Astronomy, 2021)
Comets and asteroids are considered as very dangerous objects to Earth. Machine Learning and Deep Learning tools can be used to identify and track such hazardous objects early enough prior to impact. Preparation strategies require several years, so the early detection of such hazardous objects is very crucial aspect. In this paper, the importance of using Machine Learning and Deep Learning to identify and detect asteroids and comets is discussed briefly.Â Â Â